(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2008)
Poultry is one of the major protein sources for people in Bangladesh. It is a promising sector. It requires large scale feed production activities. There are various sources of raw materials for poultry feed production. In many ways these sources can be associated with anthropogenic heavy metal pollution. It is better to monitor any probable propagation of heavy metals into the food chain through the final feeds rather than the various raw materials for feeds. Three widely used feeds - Usha, Fresh, and Saudi-Bangla feeds were selected for the study. Cadmium, lead, arsenic, mercury, selenium, chromium, manganese, nickel, copper, and zinc contents of all samples were measured. The detected maximum and minimum concentrations of these elements were found to be: 0.1852 ppm and 0.0232 ppm for cadmium, 20.6498 ppm and 0.6019 ppm for lead, 0.7640 ppm and 0.0069 ppm for arsenic, 0.0579 ppm and 0.0116 ppm for mercury, 0.0347 ppm and 0.0069 ppm for selenium, 5.7875 ppm and 0.0926 ppm for chromium, 302.2001 ppm and 0.0695 ppm for manganese, 5.1625 ppm and 0.0125 ppm for nickel, 37.5725 ppm and 0.0463 ppm for copper, and 422.3023 ppm and 0.0232 ppm for zinc. The "Poultry Feed Reference Standards, February 2002", prepared by Ministry of Fisheries and Livestock, Govt. of the People’s Republic of Bangladesh contains no standards for the heavy metals as contaminants into poultry feeds which demands immediate attention. Key words: Heavy metal, Poultry feed, Environmental health. Bangladesh J. Sci. Ind. Res. 42(4), 465-474., 2007